Crossing the Chasm – Introducing Flexible Learning into the Botswana Technical Education Programme: From Policy to Action - Mead Richardson, Alison (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This paper reports on a longitudinal, ethnomethodological case study of the development towards flexible delivery of the Botswana Technical Education Programme (BTEP), offered by Francistown College of Technical & Vocational Education (FCTVE). Data collection methods included documentary analysis, naturalistic participant observation, and semi-structured interviews. The author identifies and analyses the technical, staffing, and cultural barriers to change when introducing technology-enhanced, flexible delivery methods. The study recommends that strategies to advance flexible learning should focus on the following goals: establish flexible policy and administration systems, change how staff utilization is calculated when flexible learning methodologies are used, embed flexible delivery in individual performance development and department/college strategic plans, ensure managerial leadership, hire and support permanent specialists, identify champions and share success stories, and address issues of inflexible organisational culture. This study may be of value in developing countries where mass-based models are sought to expand access to vocational education and training.